Alternating Current - Social Innovation in Community Energy. - Colell, Arwen (Springer VS, 2021)
Community energy projects give their own answers to the challenges of energy system change: They are social innovations. By building new relations between local economies, communities and technical infrastructures, these projects not only change the energy system but also respective power structures. Drawing on case studies from Germany, Denmark and Scotland, this book shows the importance of community ties, and shared symbols for successful processes of transformation and develops recommendations for policy decision-makers.
Keywords: Energieversorgung; Energiewende; Energiesystem; Transformation; Bürgerenergie; Stromversorgung; Energieproduktion; Beispielsammlung; Soziale Innovation